Distortion correction for wide angle holographic projector - Szpygiel, Jędrzej; Chlipała, Maksymilian; Kukołowicz, Rafał; Idicula, Moncy; Kozacki, Tomasz (Photonics Letters of Poland, 2021)
This letter presents distortion correction method enabling distortion minimized, large size image in wide angle holographic projector. The technique applies numerical predistortion of an input image used for hologram generation. It is based on estimation of distortion coefficients by comparing optically reconstructed point test chart with the original one. Obtained experimental results prove that the technique allows reconstruction of high-quality image. Full Text: PDF References M. Makowski, Experimental Aspects of Holographic Projection with a Liquid-Crystal-on-Silicon Spatial Light Modulator, in Holographic Materials and Optical Systems, M. Kumar, ed. (IntechOpen, 2019). CrossRef H. Pang, A. Cao, W. Liu, L. Shi, and Q. Deng, "Effective method for further magnifying the image in holographic projection under divergent light illumination", Appl. Opt. 58, 8713 (2019). CrossRef Y. Qi, C. Chang, and J. Xia, "Speckleless holographic display by complex modulation based on double-phase method", Opt. Express 24, 30368 (2016). CrossRef E. Buckley, "Holographic Laser Projection", J. Display Technol. 99, 1 (2010). DirectLink M. Chlipała, T. Kozacki, H. Yeom, J. Martinez-Carranza, R. Kukołowicz, J. Kim, J. Yang, J. Choi, J. Pi, and C. Hwang, "Wide angle holographic video projection display", Opt. Lett. 46, 4956 (2021). CrossRef Z. He, X. Sui, L. Cao and G. Jin, "Image-Distortion Correction Algorithm for Computer-Generated Holographic Display," 2018 IEEE 27th International Symposium on Industrial Electronics (ISIE), 1331 (2018). CrossRef A. Kaczorowski, G.S. Gordon, A. Palani, S. Czerniawski and T.D. Wilkinson, "Optimization-Based Adaptive Optical Correction for Holographic Projectors", J. Display Technol. 11(7), 596 (2015). CrossRef Z. He, X. Sui, G. Jin, L. Cao, "Distortion-Correction Method Based on Angular Spectrum Algorithm for Holographic Display", IEEE Trans. Industr. Inform. 15, 6162 (2019). CrossRef O. Mendoza-Yero, G. Mínguez-Vega, and J. Lancis, "Encoding complex fields by using a phase-only optical element", Opt. Lett. 39, 1740 (2014). CrossRef T. Kozacki, K. Falaggis, "Angular spectrum method with compact space–bandwidth: generalization and full-field accuracy", Appl. Opt. 55, 5014 (2016). CrossRef